Novel mutations in KARS cause hypertrophic cardiomyopathy and combined mitochondrial respiratory chain defect. Issue 6 (17th March 2017) - Verrigni, D.; Diodato, D.; Di Nottia, M.; Torraco, A.; Bellacchio, E.; Rizza, T.; Tozzi, G.; Verardo, M.; Piemonte, F.; Tasca, G.; D'Amico, A.; Bertini, E.; et al.
Abstract : Mutations in KARS, which encodes for both mitochondrial and cytoplasmic lysyl‐tRNA synthetase, have been so far associated with three different phenotypes: the recessive form of Charcot–Mary–Tooth polyneuropathy, the autosomal recessive nonsyndromic hearing loss and the last recently described condition related to congenital visual impairment and progressive microcephaly. Here we report the case of a 14‐year‐old girl with severe cardiomyopathy associated to mild psychomotor delay and mild myopathy; moreover, a diffuse reduction of cytochrome C oxidase (COX, complex IV) and a combined enzymatic defect of complex I (CI) and complex IV (CIV) was evident in muscle biopsy. Using the TruSight One sequencing panel we identified two novel mutations in KARS . Both mutations, never reported previously, occur in a highly conserved region of the catalytic domain and displayed a dramatic effect on KARS stability. Structural analysis confirmed the pathogenic role of the identified variants. Our findings confirm and emphasize that mt‐aminoacyl‐tRNA synthetases (mt‐ARSs) enzymes are related to a broad clinical spectrum due to their multiple and still unknown functions. Abstract :